(untitled) - Maas, Sarah J. (New York, 2014)
Royal assassin Celaena must travel to a new land to confront a truth about her heritage, while brutal and monstrous forces are gathering on the horizon, intent on enslaving her world.
910L
910L
Accelerated Reader AR
Keywords: Fiction; Identity; Fiction; Assassins; Fantasy; Courts and courtiers; Juvenile fiction; Kings and rulers; Juvenile fiction; Assassins; Juvenile fiction